Perceptions of the quality of generic medicines: implications for trust in public services within the local health system in Tumkur, India. (13th January 2018) - Aivalli, Praveen Kumar; Elias, Maya Annie; Pati, Manoj Kumar; Bhanuprakash, Srinath; Munegowda, Chikkagollahalli; Shroff, Zubin Cyrus; Srinivas, Prashanth N
Abstract : Introduction: Generic medicines are an important policy option to reduce out-of-pocket expenditure on medicines. However, negative perceptions of their quality affect utilisation and raise issues of confidence and trust in medicines and health services. The aim of the study was to test the quality of generic and branded medicines and explain negative perceptions towards generic medicines. Methods: The study was part of a larger study on access to medicines. Information on various quality parameters was collected for branded medicines and branded and unbranded generic versions of the same medicines from government and private pharmacies in Karnataka in Southern India. To assess perceptions related to quality and drivers of preferred point of care (public vs private), focus group discussions were conducted with diabetes and hypertension patients, health workers and private pharmacists. The results of the quality tests were assessed and thematic analysis was conducted on the qualitative data to develop a conceptual framework to explain perceptions of medicine and care quality in the local health system. Results: The generic and branded variants of the medicines tested were of comparable quality. Contrary to the quality test results, patients' and health workers' perceptions of quality were largely in favour of branded medicines. Negative perceptions of medicine quality along with other drivers contribute towards choosing more expensive medicines in the private sector. Trust in the health system emerged as an underlying central theme that explained and drove choice of medicines and providers within the local health system. Conclusion: Negative perceptions of generic medicines and preferential promotion of branded medicines over generics by pharmaceutical companies could influence prescriber behaviour and affect trust in healthcare provided in public services. To succeed, access to medicines programmes need to systematically invest in information on quality of medicines and develop strategies to build trust in healthcare offered in government health services.